DIVERSITY OF SWALLOWTAL BUTTERFLY SPECIES (RHOPALOCRA, PAPILIONIDAE) IN THREE PROTECTED AREAS OF THUA THIEN HUE PROVINCE - Van Lien, Vu; Quynh Trang, Le; L. Häuser, Christoph; Dinh Ba, Vo; Dinh Duc, Bui (Journal of Forestry Science and Technology, 2019)
The study on swallowtail butterflies (Papilionidae) of three protected areas of Thua Thien Hue province was carried out sometimes between April and June from 2015 to 2018, at different habitats and altitudes in Bach Ma National Park (NP), Phong Dien Nature Reserve (NR), and Sao La Nature Reserve (NR). Butterflies were observed and collected randomly by insect nets in the surveyed areas. In additional, butterfly species were also referred from previous works on butterflies in the area to make a list of Papilionidae species. The similarity of species composition between three protected areas was analyzed with Cluster Analysis by Primer V5. Total 36 species of the Papilionidae family has been recorded in three protected areas. There are 4 species listed in the Red Data Book of Vietnam (2007): Troides helena, T. aeacus, Teinopalpus aureus, and Papilio noblei. Among them, first three species are listed in the CITES (2018). Teinopalpus aureus is in the Red List of IUCN (2018). The similarity of species composition between protected areas is rather high (67%), highest between Phong Dien NR and Sao Lao NR (69.8%). The species composition of Bach Ma NP is slightly different from Phong Dien NR and Sao La NR as Bach Ma NP has 7 species not found in two other protected areas. Bach Ma NP has high conservation value of butterfly species as where has the most species number (32 species) and the most protected species (4 species).